Transformasi Digital Administrasi Sekolah: Strategi Inovatif dalam Meningkatkan Excellent Service - Abdul Jalil (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
Digital transformation in school administration has become an urgent need to improve the efficiency and quality of educational services. This study was conducted to determine the implementation of innovative strategies in the digitalization of school administration systems as an effort to improve excellent service. This study used a descriptive qualitative research method with a case study research type to explore digital strategies in school administration. In-depth interviews were the step in collecting data at Mts Ibadurrahman Wae Tuo. The results of this study indicate that the implementation of a digital administration system in schools was carried out in response to the needs of parents, the majority of whom are from Generation Z and millennials. This group has a high tendency to access information and services digitally to obtain ease in service. Therefore, the school innovated by developing an administration system that can be accessed digitally as an effort to realize excellent service. The innovation strategies implemented by this institution include the use of digital technology, including the use of a digital attendance management system, the IDN application for tuition payments and student registration, the implementation of online New Student Admissions (PPDB), and the provision of an official website and call center services as a communication medium between the school and parents. The implementation of this digital-based excellent service can run optimally because it is supported by the availability of adequate school infrastructure.